FAKTOR-FAKTOR YANG MEMPENGARUHI KOMPENSASI EKSEKUTIF DAN HUBUNGANNYA DENGAN KINERJA PERUSAHAAN: KASUS BUMN PERKEBUNAN - Dyan Vidyatmoko; Bunasor Sanim; Hermanto Siregar; M. Said Didu (School of Business, Bogor Agricultural University (SB-IPB), 2009)
The objectives of this research are (1) to analyse determinants and the magnitude of the influencing factors of the Indonesian Estate State-owned enterprises’ executive compensations; and (2) to analyse the relationship between those influencing factors with firm performances, statistical methods used for analysing these objectives are Structural Equation Model (SEM), contingency analysis, regresion analysis and qualitative analysis. The study found out that from all identified variables, executive decision mechanism, job complexity, firm size, firm ability to pay compensation, and product diversification and market expansion have positive correlation and significant influenced to executive compensation. Human capital, business risk, executive employment market have significant correlations to executive compensation. The research has shown that firm size has positive correlation and significant influenced towards customers performance, internal business process performance, and growth and learning performance. Firm ability to pay has positive correlation and significant influenced towards financial performance, customer performance and growth and learning performance. Product diversity and market expansion has positive correlation and significant influence to customer performance and internal business process performance.